2015
DOI: 10.1155/2015/792819
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of LpGPAT Gene inLilium pensylvanicumand Response to Cold Stress

Abstract: LpGPAT was obtained from L. pensylvanicum using RT-PCR and rapid amplification of cDNA ends. The cloned full-length cDNA was 1544 bp; it encoded 410 amino acids and had a molecular size of 46 KDa. The nucleic acid sequence analysis showed that it shared high homology with other known GPATs. SMAT result suggests that there is a PlsC that exists in 176-322 amino acid sequence of LpGAPT; it means LpGPAT protein is a member of the family of acyltransferase and has acyltransferase enzymatic activity. Result of real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…The GPAT gene family has been identified in many model plants, including Arabidopsis thaliana [ 8 , 10 ], Brassica napus [ 11 ], Oryza sativa [ 10 ], Zea mays [ 12 ], and other plants, such as Paeonia [ 13 ], Gossypium [ 14 ], and Perilla frutescens [ 15 ]. It has been confirmed that the members of the GPAT gene family have been widely described for their role in male fertility [ 16 , 17 , 18 , 19 , 20 , 21 ], seed development [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], biotic and abiotic stress tolerance [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], and cuticle or suberin production [ 5 , 22 , 44 , 45 , 46 , 47 , 48 , 49 ]. At present, the research on the GPAT gene family is the best in the model plant Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GPAT gene family has been identified in many model plants, including Arabidopsis thaliana [ 8 , 10 ], Brassica napus [ 11 ], Oryza sativa [ 10 ], Zea mays [ 12 ], and other plants, such as Paeonia [ 13 ], Gossypium [ 14 ], and Perilla frutescens [ 15 ]. It has been confirmed that the members of the GPAT gene family have been widely described for their role in male fertility [ 16 , 17 , 18 , 19 , 20 , 21 ], seed development [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], biotic and abiotic stress tolerance [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], and cuticle or suberin production [ 5 , 22 , 44 , 45 , 46 , 47 , 48 , 49 ]. At present, the research on the GPAT gene family is the best in the model plant Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…The function of GPAT genes under abiotic stresses such as drought, salinity, low temperature, and high temperature has been studied in many plants [ 33 , 34 , 36 , 37 , 38 , 40 , 41 , 43 , 53 ]. It is reported that the overexpression of the AtS1 gene improves the tolerance of Arabidopsis seedlings to low temperature stress, while the transformation of the squash GPAT gene into tobacco leads to a reduction in low temperature tolerance [ 31 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis, ten GPAT homologs have been identified, of which GPAT1~8 are the land-plant-specific sn-2-GPAT that is mainly involved in the biosynthesis of lipid polyesters such as cutin and suberin, and is associated with plant flower development and stress response (Li et al, 2007;Li-Beisson et al, 2009;Chen et al, 2011;Yang et al, 2012). Plastid-localized ATS1 also can catalyze the acylation reaction at the sn-1 site of G3P using acyl-ACP as an acyl donor, and may be related to the mechanism of plant cold tolerance response (Paya-Milans et al, 2015;Sun et al, 2015). Loss of function of GPAT1 located in mitochondria alters the fatty acid composition in floral tissues and seeds, but its effect on seed oil content is still controversial (Zheng et al, 2003;Bai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…qRT-PCR is commonly used to analyze gene expression in Lilium . To date, the traditional housekeeping genes UBQ [ 31 ], GAPDH [ 32 , 33 ], 18S [ 21 ], and ACT [ 2 , 34 , 35 ] have been used as internal reference genes to standardize the expression profile of some genes. However, the relative stability of these and other potential reference genes in Lilium has not been validated in a range of experimental contexts, and this has constrained the wider use of qRT-PCR in Lilium .…”
Section: Introductionmentioning
confidence: 99%